Sosialisasi Perhitungan Harga Pokok Penjualan Bagi UMKM Kelurahan Kalijudan - Condro Widodo; Aliya Murthi Arifah; Anggi Krisnawati; Lila Amelia Safitri; Wanda Ayu Oktavia; Yuanita Belva Chatlina (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
Micro, Small and Medium Enterprises (MSMEs) play an important role as a driver of Indonesia's economy. The management of MSMEs in Indonesia has the problem of limited knowledge to calculate the right cost of goods sold because they do not understand the concept of Cost of Goods Sold (COGS). To deal with these problems, MSME actors need to understand the concept of COGS Sold to optimize profits and minimize business losses. This research method is descriptive with a qualitative approach. The data collection techniques used are literature studies and field studies. Meanwhile, the community service analysis technique consists of the preparation stage, the implementation stage and the evaluation stage. The result of this research from community service is to provide relevant knowledge to the community about the urgency of financial records in entrepreneurship. Through this activity, the public's understanding of the concept of COGS in optimizing MSME businesses has increased